Clinicopathological correlation of leprosy and response to treatment in Eastern Saudi Arabia - Omar M Alakloby; Adnan Suliaman Alabdulkareem; Salih Hamad M Aljabre; Mohammad A Randhawa; Esra Omar Alakloby; Abdullah Salih Aljabr; Afnan Majed Almutairi (Wolters Kluwer Medknow Publications, 2019)
Background: Leprosy is a chronic, progressing, and disabling disease caused by Mycobacterium leprae, predominantly affecting the skin and peripheral nerves. Aim: The aim is to study clinicopathological correlation and response to treatment in leprosy patients attending King Fahd Hospital of University (KFHU), Al-Khobar, Eastern Saudi Arabia. Methodology: Records of all cases attending Dermatology Department of KFHU from 1985 to 2005 and labeled clinically as leprosy were retrieved. Their clinical data and histopathologic slides were reviewed. Many of the expatriates left Saudi Arabia after diagnosis. The remaining ones and Saudi nationals received the WHO standard treatment for 12 months and 18 months for paucibacillary and multibacillary leprosy, respectively. Results: Among 87 cases, there was a good clinicopathological correlation; the most common forms of leprosy clinically and histologically were of borderline leprosy (BB), 31 (35.63%) and 34 (39.08%), followed by tuberculoid type (TT), 22 (25.29%) and 27 (31.03%); lepromatous leprosy, 18 (20.69%) and 17 (19.54%); erythema nodosum leprosum (ENL), 6 (6.9%) and 5 (5.75%); indeterminate leprosy, 4 (4.6%) and 4 (4.6%); and nonspecific, 6 (6.9%). Thirty-two patients received the WHO standard treatment for paucibacillary and multibacillary leprosy, respectively; all cases showed complete clinical improvement with 24-month follow-up, except for two paucibacillary cases who developed ENL and lost follow-up after 16 months. Conclusions: There was a good clinicopathological correlation. The response to treatment was good in those who continued treatment and better in TT than lepromatous type of leprosy.